2022
DOI: 10.51477/mejs.1166842
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pre-Eclampsia Complicated by Hellp Syndrome in the Hoffbauer and Syncytiotrophoblast Cells (Ultrastructural and Immunohistochemical Study)

Abstract: The aim of this study was to evaluate the immunohistochemistry and ultrastructural of syncytiotrophoblast and Hoffbauer cells in placental villi of HELLP syndrome patients. Placental samples with twenty control (normotensive) and twenty HELLP syndrome were fixed in 10% neutral formalin solution for paraffin-embedding wax protocol. Placental samples were fixed in 2.5% buffered glutaraldehyde and then, in 1% osmium tetra oxide for routine electron microscopic procedure. When the HELLP group fetal placental secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the histopathology of placenta, intervillous thrombosis, abruption and infarction were more common in women with HELLP syndrome. Nergiz et al 23 found that Hoffbauer cells were increased in placenta of HELLP syndrome. In their ultrastructural analysis, degenerative structure in cell surface membrane, intracytoplasmic edema, and degenerative vacuoles in syncytiotrophoblast were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…In the histopathology of placenta, intervillous thrombosis, abruption and infarction were more common in women with HELLP syndrome. Nergiz et al 23 found that Hoffbauer cells were increased in placenta of HELLP syndrome. In their ultrastructural analysis, degenerative structure in cell surface membrane, intracytoplasmic edema, and degenerative vacuoles in syncytiotrophoblast were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…HELLP syndrome and preeclampsia can have a familial tendency. In this regard, Nergiz et al [5] reported a significant increase in placental Hoffbauer cells, syncytiotrophoblast cell counts as well as several ultrastructural changes that were observed in the HELLP group compared with the control group. HELLP occurs in less than 1% of pregnancies and, in most cases, coexists with preeclampsia.…”
mentioning
confidence: 95%